Reducing Catastrophic Health Costs: The Role of Public Insurance in Eastern Indonesia - Intan Solikhah Indriana; Romi Bhakti Hartarto (Jurnal Ekonomi Pembangunan)
Catastrophic expenditure, defined as health care expenditure exceeding 10% of household income, remains prevalent in eastern Indonesia, highlighting the urgent need for targeted health policy and infrastructure interventions. This study investigates the impact of the Community Health Insurance Scheme (Jamkesmas) in reducing catastrophic healthcare expenditure in eastern Indonesia offering a new perspective by focusing on areas with lower Universal Health Coverage (UHC) and higher poverty rates. Using data from the 2012 Eastern Indonesia Family Life Survey covering a sample of 1,105 working-age individuals, logit and probit regression methods were applied. The findings revealed that Jamkesmas significantly reduced the likelihood of catastrophic health care expenditure, with effectiveness 1.8 times higher than that of individuals without health insurance. Exogenous factors such as age, urban residence, male gender, and marital status further supported this reduction. In contrast, barriers such as long distances to health facilities and limited knowledge of public hospitals increased the risk of catastrophic expenditure among workers. These results underscore the importance of expanding access to health services and improving the implementation of Jamkesmas in eastern Indonesia. By addressing disparities in health insurance coverage and healthcare facility distribution, the government can better mitigate catastrophic expenditures, supporting the achievement of the demographic bonus by 2045.